Efforts in Securing Vaccine for Covid-19 Outbreak in Indonesia - I Dewa Agung Panji Dwipayana (Humanistic Network for Science and Technology (HNST), 2020)
Indonesia already achieved the highest COVID-19 death rate in South East Asia. Securing enough vaccine is the only way to eradicate this disease by commencing mass vaccination. Therefore, this review is aimed to discuss Indonesia’s readiness to commence mass COVID-19 vaccination, discussed from biomedical, socioeconomic, and regulatory approach. An extensive literature study was done in focus to gather the latest information regarding to the efforts made by Indonesia to secure adequate supply of vaccine. Through international collaboration, Indonesia has established several vaccine-related cooperation with multiple organizations. Independently, Indonesia is trying to develop “Merah Putih” vaccines covering 6 parallel local vaccine research. The combined Indonesian efforts may secure around 300 million vaccine doses, whereas the government aims to vaccinate at least 70% of its population to gain herd immunity. If each person needs 2 vaccine doses, then the currently secured vaccines is not yet enough to fill the 376 million doses demand. It can be concluded that Indonesia still needs to secure another 100 million doses before it is ready for commencing mass COVID-19 immunization. Keywords: COVID-19; mass immunization; Indonesia; readiness; vaccine